Neonatal subpial hemorrhage along the medial side of the temporal lobe: Two case reports - Naoko Matsubara, MD (Radiology Case Reports, 2022)
Neonatal subpial hemorrhage has been underrecognized until recently and its pathophysiology remains unclear. Advances in magnetic resonance imaging have facilitated the identification of hemorrhage within the subpial space and cohort studies recently reported its imaging and clinical features. We encountered two cases of neonatal subpial hemorrhage along the medial side of the temporal lobe. Case 1: A 1-day-old boy had repeated apneic attacks with cyanosis from 2 hours after birth at 39 weeks of gestation by vacuum extraction delivery. Computed tomography and magnetic resonance imaging showed subpial hemorrhage from the medial to caudal side of the right temporal lobe with T2 prolongation in the underlying cerebral parenchyma. Case 2: A 0-day-old boy had repeated apneic attacks with cyanosis from 3 hours after birth at 39 weeks of gestation by vaginal delivery. Subpial hemorrhage was observed from the anterior to medial side of the left temporal lobe on computed tomography and magnetic resonance imaging. On magnetic resonance imaging, the adjacent brain parenchyma showed a hyperintense signal on T2-weighted imaging. No abnormalities or signs of fetal distress were noted in the course of delivery. A mildly prolonged activated partial thromboplastin clotting time, an elevated D-dimer level, and low fibrinogen level were detected in a blood examination after birth in both cases. Both cases had subpial hemorrhage along the medial side of the temporal lobe, which suggested that an external mechanical force with fetal head molding during delivery caused subpial hemorrhage; however, other factors, including coagulopathy, may be involved in its pathophysiology.